The relationship between physical activity and depression among community-dwelling adults in Wuhan, China - Wu, Kai-Ge; Chen, Si-Jing; Hu, Ya-Ni; Mei, Shu-Fang; Chen, Wen-Cai; Huang, Xian-E; Xu, Zai-Feng; Li, Ming-Chao; Zhong, Bao-Liang; Liu, Xiu-Jun (Frontiers in Psychiatry, 2023)
Background: Physical activity (PA) is a critical factor for depression, but limited studies have investigated the effect of PA on Chinese. This study aims to explore the associations of PA and depression among Chinese individuals aged 18 years and older. Methods: The stratified random sampling approach was conducted to include study subjects from five urban districts in Wuhan, China. A total of 5583 permanent residents aged 18 years or older completed questionnaires. International Physical Activity Questionnaire Short Form (IPAQ-SF) was used to measure PA. The 9-item Patient Health Questionnaire (PHQ-9) was used to evaluate depressive symptoms. Multivariable logistic regression was used to estimate the odds ratios (ORs) of PA levels on depression while adjusting for potential confounders. Results: Compared to the non-depression group, the weekly PA levels of the depression group were significantly lower (2772 (1324-4893) MET-min/w, 1770 (693-4200) MET-min/w, P < 0.001). In fully adjusted model, referred to the low PA level group, the moderate and high PA level groups reported lower ORs for depressive symptoms (OR: 0.675, 0.623; 95% CI (95% confidence interval): 0.528-0.864, 0.488-0.795), P for trend < 0.001. The risk of depression was observed lower in male individuals with moderate and high levels of PA, compared to those with low PA levels (OR: 0.419, 0.382; 95% CI: 0.271-0.648, 0.246-0.594). However, the association was not observed in females (OR: 0.827, 0.780; 95% CI: 0.611-1.120, 0.578-1.052). A significant interaction between PA levels and gender in the role of depression was found (P for interaction < 0.05). Conclusion: Our findings indicated that there was a negative relationship between PA and depression. Moderate to high levels of PA might play a protective role for depressive symptoms.